Inequitable Utilization of Neonatal Health Services in Southwest Ethiopia: The Effects of Socioeconomic Disparities - Kiddus Yitbarek; Sarah Hurlburt; Terje P. Hagen; Melkamu Berhane; Gelila Abraham; Ayinengida Adamu; Gebeyehu Tsega; Mirkuzie Woldie (SAGE Publishing, 2021)
Low levels of neonatal health services utilization and high neonatal deaths are often concentrated among socially and economically disadvantaged groups, especially in low-income countries. Therefore the aim of this study was to assess inequity in the use of neonatal health services in Southwest Ethiopia. A community-based cross-sectional study was conducted in 8 districts located in Jimma Zone, Southwest Ethiopia from 19 March to 28 April 2018. A total of 835 mothers were included in the study with systematic random sampling. Principal component analysis was conducted to develop wealth quintiles of the households. Equity in neonatal health services was measured using rate-ratio, concentration curve, concentration index, and analyzed by binary logistic regression. Neonates from richer families were 1.25 times more likely to use neonatal health services than the poorer households with a concentration index value of 0.07. Neonates from highly educated mothers have better used the services and the corresponding concentration index value of 0.03. Neonatal service utilization was 1.32 times higher in the highest wealth quintile in rural settings. Similarly, services delivered at health posts and hospitals were used 2.4 and 2 times more by the wealthy, whereas services given at health centers are more utilized by the poorest. Outputs of binary logistic regression analysis indicated that neonates from middle quintile wealth households were found to be better neonatal health service users [AOR_1.72, 95% CI: 1.04, 2.82]. Neonate born from a secondary school attended mother [AOR_3.56, 95% CI: 1.90, 6.69] were more likely to use neonatal health services. Neonatal health service utilization in Southwest Ethiopia is more common among neonates from richer households and more educated mothers. There is a big difference among the wealthy and poorer in a rural setting and among those who used health posts. Working on the social-determinants of health will facilitate eliminating inequity.